Changing Party Systems, Socio-Economic Cleavages, and Nationalism in Northern Europe, 1956-2017 - Martinez-Toledano, Clara; Sodano, Alice (HAL CCSD, 2021)
This paper draws on a rich set of electoral surveys to explore the changing relationship between party support and electoral socioeconomic cleavages in Denmark, Finland, Iceland, Norway, and Sweden from the mid-twentieth century until the present. All five countries have experienced a progressive decline in their strong class cleavages, which coincides with the emergence of multi-elite party systems, in line with most Western democracies. While in the 1950s-1960s the lowest-educated and lowest-income voters were more leftwing, since the 1970s-1980s the vote for the left has gradually become associated with the highest-educated voters, who have drifted apart from the more right-wing economic elites. We also investigate how this transformation relates to the success of populism and nationalism over the recent decades among the lowest-educated and lowest-income earners. Despite historical, cultural, and political links, the transition of Nordic countries towards a multi-elite party system has happened at different speeds, offering interesting insights on the specificities of the national trajectories.